An Ultraviolet‐to‐NIR Broad Spectral Nanocomposite Photodetector with Gain. Issue 6 (8th April 2014) - Dong, Rui; Bi, Cheng; Dong, Qingfeng; Guo, Fawen; Yuan, Yongbo; Fang, Yanjun; Xiao, Zhengguo; Huang, Jinsong
<x xml:space="preserve">Abstract</x> A PbS‐based NIR hybrid photodetector with an external quantum efficiency (EQE) above 100% is created by integrating zinc oxide (ZnO) quantum dots (QDs) to induce a photoconductive gain. The dual‐QD hybrid photodetector also shows a tenfold higher responsivity than that of commercial SiC and Si photodetectors in the UV–visible range at room temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>